2010
DOI: 10.1007/s11255-010-9714-y
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal dialysis in the nursing home

Abstract: Our results with elderly patients in a nursing home show an excellent patient and technique survival and a low peritonitis rate. With appropriate training of the NH nursing staff, peritoneal dialysis could be performed successfully in these nursing homes. Successful peritoneal dialysis in a nursing home requires a close collaboration between the nursing home staff and PD dialysis unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…There are several reports of successful PD for nursing-home residents [27,28]. In areas where aPD is available to support patients within their homes, 75% of those who chose PD received aPD compared to self-care PD.…”
Section: Home-based Dialysis Solutions For the Elderlymentioning
confidence: 99%
“…There are several reports of successful PD for nursing-home residents [27,28]. In areas where aPD is available to support patients within their homes, 75% of those who chose PD received aPD compared to self-care PD.…”
Section: Home-based Dialysis Solutions For the Elderlymentioning
confidence: 99%
“…The lowest survival rates (i.e., 38%) were reported by Reddy et al in a study of HD patients in which nearly half of the cohort (47%) had initiated HD within 3 months of NH admission 13 . A higher survival rate (i.e., 56%) was reported in a mixed cohort of HD and PD patients in whom only 25% had initiated dialysis within 3 months of admission 11 , while the most favorable survival rate (i.e., 61%) was found in a Canadian population with a median dialysis duration of 31 months 9 . This association was further characterized by Reddy et al in an analysis of survival time according to length of time on HD 13 .…”
Section: Resultsmentioning
confidence: 89%
“…The majority of studies (9 of 14) encompassed study periods between 1985 and 2000. Most studies had multicenter cohorts from various NHs located in the United States, while two studies examined outcomes in NHs located in Toronto, Canada 8,9 . Mean subject age ranged from 63 to 83 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in a recent paper, Taskapan et al [32] found a lower rate (5.3%) of transfer from PD to HD and of peritonitis rate (1 episode every 40.3 treatment-months) in PD patients in the nursing home. The differences were possibly the result of better care by the nursing home staff.…”
Section: Discussionmentioning
confidence: 89%